Roles of Individual Institutions in Achieving Pharmaceutical Sovereignty as Exemplified by the Medical Technology Transfer Centre of the Scientific Centre for Expert Evaluation of Medicinal Products - A. S. Koshevenko; T. V. Degrave; P. V. Burenkov; K. Yu. Belanov; V. V. Kosenko (Регуляторные исследования и экспертиза лекарственных средств)
INTRODUCTION. The strengthening of the health system and the improvement of access to medicines directly depend on the development and marketing authorisation of national innovative medicinal products. Technology transfer is a key tool in bringing medicinal products to market.AIM. This study aimed to evaluate the role of the Medical Technology Transfer Centre of the Federal State Budgetary Institution ‘Scientific Centre for Expert Evaluation of Medicinal Products’ of the Ministry of Health of the Russian Federation (FSBI ‘SCEEMP’) in facilitating the implementation of federal projects in medical science and in achieving of pharmaceutical sovereignty.DISCUSSION. This article is an overview of the main trends in and features of the development of the pharmaceutical industry in the Russian Federation and around the world. The article highlights significant federal decisions made to attain pharmaceutical sovereignty and improve access to medicines for the population. The authors consider documents regulating the work of the Medical Technology Transfer Centre and outline its roles and responsibilities. Additionally, the authors analyse the ability of the Medical Technology Transfer Centre to provide project support throughout the medicinal product development process and to address issues pertaining to efficient pharmaceutical development, patent law, and product commercialisation. The article assesses the role of the Medical Technology Transfer Centre in the development of the pharmaceutical industry in the Russian Federation.CONCLUSIONS. The Medical Technology Transfer Centre supports projects as part of efforts to implement federal projects in human medical science. The Medical Technology Transfer Centre can be considered a driver of effective innovative development in the national pharmaceutical industry.